VALIDATING COMMUNITY OF INQUIRY FRAMEWORK in ADULT LEARNINGFINDINGS from an EMPIRICAL INVESTIGATION in a UNIVERSITY ORGANIZED LITERACY PROGRAMME in Nigeria - Kester Osegha Ojokheta (Adult Education Research Conference, 2015)
Community of Inquiry (CoI) Framework is one of the leading models guiding online teaching and learning. There is the general consensus that the framework enhances learning outcomes and provides meaningful support among learners. This study was conducted to ascertain the validity of the CoI in adult literacy programme in Nigeria.
Keywords: validating; community-of-inquiry-framework; adult learning; university-literacy programme